2011
DOI: 10.1016/j.taap.2010.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Functional and inflammatory alterations in the lung following exposure of rats to nitrogen mustard

Abstract: Nitrogen mustard is a vesicant that causes damage to the respiratory tract. In these studies, we characterized the acute effects of nitrogen mustard on lung structure, inflammatory mediator expression, and pulmonary function, with the goal of identifying mediators potentially involved in toxicity. Treatment of rats (male Wistar, 200–225 g) with nitrogen mustard (mechlorethamine hydrochloride, i.t., 0.25 mg/kg) resulted in marked histological changes in the respiratory tract, including necrotizing bronchiolitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
90
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 41 publications
13
90
1
Order By: Relevance
“…NM-induced pulmonary toxicity is characterized by prominent histopathologic alterations in the lung including inflammatory cell accumulation, edema, fibrin deposition, bronchiolar and alveolar epithelial hyperplasia, bronchiectasis, fibroplasia and emphysema, along with increases in BAL protein and cells, which is in accord with previous studies (Malaviya et al, 2012; Sunil et al, 2011b). Pentoxifylline post-treatment significantly attenuated histologic evidence of pulmonary inflammation and injury, as well as increases in BAL protein and cell content.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…NM-induced pulmonary toxicity is characterized by prominent histopathologic alterations in the lung including inflammatory cell accumulation, edema, fibrin deposition, bronchiolar and alveolar epithelial hyperplasia, bronchiectasis, fibroplasia and emphysema, along with increases in BAL protein and cells, which is in accord with previous studies (Malaviya et al, 2012; Sunil et al, 2011b). Pentoxifylline post-treatment significantly attenuated histologic evidence of pulmonary inflammation and injury, as well as increases in BAL protein and cell content.…”
Section: Discussionsupporting
confidence: 90%
“…Of particular interest is tumor necrosis factor (TNF)α, a macrophage-derived pro-inflammatory cytokine rapidly generated in the lung in response to injury induced by vesicants (Malaviya et al, 2010; Sunil et al, 2011b; Sunil et al, 2012). The major receptor mediating the pro-inflammatory activity of TNFα is TNFR1 (Parameswaran and Patial, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NO and peroxynitrite oxidize and covalently modify membrane lipids, thiols, proteins, and DNA, inducing cytotoxicity and perpetuating inflammation. In another study, it has been demonstrated that the expression of iNOS was rapidly up-regulated in alveolar macrophages following MEC exposure [31]. iNOS is predominantly expressed in inflammatory cells such as macrophages in affected tissues.…”
Section: Discussionmentioning
confidence: 91%
“…Our findings that M1 and M2 macrophages sequentially accumulate in the lung following NM exposure, and that their appearance correlates with acute injury and fibrosis, suggest that they may contribute to these pathogenic responses. (13). In earlier studies, we found that this dose of NM is effective in inducing acute lung injury, which progresses to fibrosis without significant mortality (6).…”
Section: Clinical Relevancementioning
confidence: 89%